2009
DOI: 10.2306/scienceasia1513-1874.2009.35.024
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cleansing lotion containing 8% w/w tamarind pulp extract was prepared and tested for its clinical effects on skin properties. The study was performed using 38 healthy Thai female volunteers, and consisted of a home-use, doubleblind, randomized side of face and placebo controlled trial. The test product (emulsion with the extract) and the placebo product (emulsion without the extract) were applied and gently massaged on each side of facial skin for 2 minutes twice daily for 8 weeks and the difference in skin co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In women volunteers, a cleansing lotion containing tamarind fruit extract (10 % w/w) applied twice daily for when compared to the other side of the face. Also, there was no erythema or transdermal water loss, showing that the product was safe 77,78 . Previous research has shown that applying a polyherbal gel containing tamarind extract for 12 weeks reduced the stiffness, thickness, pigmentation, and irregularity of post-surgical scar development in patients who had bilaterally symmetric procedures 79,80 .…”
Section: Journal Ofmentioning
confidence: 90%
“…In women volunteers, a cleansing lotion containing tamarind fruit extract (10 % w/w) applied twice daily for when compared to the other side of the face. Also, there was no erythema or transdermal water loss, showing that the product was safe 77,78 . Previous research has shown that applying a polyherbal gel containing tamarind extract for 12 weeks reduced the stiffness, thickness, pigmentation, and irregularity of post-surgical scar development in patients who had bilaterally symmetric procedures 79,80 .…”
Section: Journal Ofmentioning
confidence: 90%
“…The wound healing property of Aloe vera gel has been attributed to Mannose-6-phosphate used for fi rst to second degree burns, (Davis et al, 1994;Maenthaisong et al, 2007).Wound healing is a dynamic process, occurring in 3 phases. The fi rst phase is infl ammation, hyperaemia and leukocyte infi ltration.…”
Section: Wound Healingmentioning
confidence: 99%